Penerapan Data Mining Dengan Metode Support Vector Machine Untuk Prediksi Cuaca - Fau, Idrianis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Cuaca is a natural phenomenon that greatly impacts humans. Information about weather prediction is needed by humans and especially in Medan City. This information is very useful to know the weather events around us. Data mining is a process of collecting important information on large data, so that it can help to make decisions and can make accurate predictions. So that researchers are interested in conducting research in predicting weather in Medan City by using the Support Vector Machine (SVM) method as a solution in predicting weather in Medan City. The application of data mining using the SVM method helps produce the right accuracy for weather based on predetermined criteria, this method is suitable for weather prediction because it is able to provide a clear and accurate assessment.